Application of the detailed assessment of speed of handwriting (dash) to brazilian students - Cardoso, Monique Herrera [UNESP]; Capellini, Simone Aparecida [UNESP] (My University, 2018)
This chapter aims to present the speed of writing, according to readability, of Brazilian public school students. Thus, the Brazilian Adaptation of the Detailed Assessment of Speed of Handwriting was applied to 658 students of both genders, aged from 09 to 16 years and 11 months, of 05 public schools. The legible words were identified by means of analyzes carried out by expert judges in handwriting, and the illegible ones were excluded. The speed calculation took into account only the legible words, divided by the time of each proposed task. It can be observed that: in general, the writing speed increases according to the increase of the age group; 12-year-old students present lower writing speed during copy activities when compared to younger students; students aged from 14 to 15 years, present lower writing speed during free-writing and quick-graph activities when compared to younger students; the cognitive and linguistic requirements in each task of the procedure are different, which resulted in the decrease of the writing speed, according to each task. The present findings contemplate the expected results, in terms of written proficiency for each age group, however, new studies on the reliability and validity of the instrument for the Brazilian population are necessary.
Keywords: Assessment; Manual writing; Speech therapy